ROOTING OF Baccharis trimera CUTTINGS ACCORDING TO DIFFERENT SUBSTRATES AND STEM POSITIONS ON MALE AND FEMALE PLANTS - CARVALHO, Ruy Inacio Neiva de; NOLASCO, Marcelo Antunes; CARVALHO, Tobias; RIPKA, Márcio; GIUBLIN, Luthy Milano; NEGRELLO, Marcel; SCHEFFER, Marianne Christina (Scientia Agraria, 2007)
The rooting of Baccharis trimera cuttings is influenced by several internal and external factors. The objective of this work was to evaluate the influence of the substrate, the stem position and the sex of the plant in the rooting of B. trimera cuttings. The work was realized in two stages in a greenhouse. The first research was realized with vegetative cuttings collected on July, 2001, in Tijucas do Sul, Paraná, Brazil, and the sex of the plant was not identified. The rooting of three original positions of cuttings in the plant (basal, middle and apical) were analysed in differents substrates prepared by the mixture of soil, vermiculite and worm compost in the following proportions (v:v): only soil; soil + vermiculite (1:1); soil + worm compost (1:1) and soil + vermiculite + worm compost (1:1:1). The second research was realized with basal and apical cuttings in the reprodutive stage collected on May, 2005, in São José dos Pinhais, Paraná, Brazil. The evaluations were done by the rooting percentage and the dry mass of roots and sprouts. The cuttings of Baccharis trimera collected in Tijucas do Sul presented high rooting percentage (94,5%) and it was not influenced by the type of substrate and the original cutting position in the plant. The worm compost is indicated to be used like a substrate conditioner to the B. trimera propagation by cuttings because the best vegetative growth. Basal cuttings of the female plants collected in São José dos Pinhais presented the best rooting quality in relation to the rooting percentage and the mass of roots produced.